A Concise Guide to Writing a Thesis or Dissertation: Educational Research and Beyond, 2nd edition - Kornuta, Halyna M. (Routledge, 2020)
A Concise Guide to Writing a Thesis or Dissertation provides clear, succinct, and intentional guidelines about organizing and writing a thesis or dissertation. Part I provides an overview for writing a thesis or dissertation. It describes the big picture of planning and formatting a research study, from identifying a topic to focusing on writing quality. Part II describes the framework and substance of a research study. It models the pattern generally found in a formal, five-chapter research study.